Blendas de biodiesel: propriedades de fluxo, estabilidade térmica e oxidativa e monitoramento durante armazenamento - Dantas, Manoel Barbosa (2010)
The Brazilian biodiesel, whatever the source of their raw materials must meet some physical and chemical parameters that ensure their quality. A major problem associated with the use of biodiesel, especially prepared with castor oil, is its high viscosity that is outside the limit set by the ANP, becoming viable as fuel, only when used as a blend to diesel or other biodiesel with lower viscosity. The soybean biodiesel presents a high percentage of esters of polyunsaturated fatty acids being more susceptible to oxidation when compared to castor oil biodiesel. Within this context, the blends of ethylic biodiesel from soybean and castor oil (BsMx) in natura and in different storage conditions are promising in the correction of the flow properties and oxidative stability. The GC-MS results confirmed the presence of 42.45% of ethyl linoleate and 85.83% of ethyl ricinoleate for the ethylic biodiesel from soybean and castor oil, as major components, respectively. The infrared spectra showed increased content of castor oil biodiesel in the blend by more intense absorption at 3440.7 cm-1. The presence of ethyl ricinoleate in higher concentration in the blend conditioned the better oxidative stability, therefore, there was a decline in the pour point. Blends with proportions of until 30 and 57% were within the limit established by the ANP for kinematic viscosity and density, respectively. The condition and storage time of 120 days caused changes decreasing induction period and increasing the acidity index, water content and kinematic viscosity, being more evident for samples stored under light. During storage of 120 days, the density, the cold filter plugging point, the cloud point and the pour point were barely affected, with only a slight increase more pronounced for samples stored under light. Blends of ethylic biodiesel from soybean and castor oil allowed the use of oil in the composition of a new biodiesel (BSM) to be blended with diesel oil within the limits established by ANP for viscosity.